Evaluation of a point‐of‐care ultrasound curriculum taught by medical students for physicians, nurses, and midwives in rural Indonesia. Issue 3 (26th December 2019) - Dornhofer, Kyle; Farhat, Ahmed; Guan, Kevin; Parker, Erica; Kong, Christina; Kim, Daniel; Nguyen, Thalia; Mogi, Jennifer; Lahham, Shadi; Fox, John C.
Abstract: Purpose: In the Indonesian health‐care system, nurses and midwives often serve as the primary health‐care providers due to physician shortages. Seeking to address the need for medical care in resource‐limited environments, some have advocated for portable equipment in the hands of health‐care providers. We hypothesized that medical students are able to effectively teach point‐of‐care ultrasound (POCUS) to physicians, nurses, and midwives in rural Indonesia. Methods: We conducted a prospective, observational study using health‐care practitioners from a clinic and accredited school for nursing and midwifery in Mojokerto, East Java, Indonesia. Enrolled practitioners took part in a 4‐week POCUS course followed by postinstructional testing. Results: A total of 55 health‐care practitioners completed the course. This included 19 physicians, 13 nurses, and 19 midwives. Of the 55 clinicians, 43 (72%) passed the course and 12 (28%) failed. Conclusions: Physicians, nurses, and midwives in rural Indonesia showed significant acquisition of ultrasound (US) knowledge and skills following a 4‐week US course. Following training, all three groups displayed skills in practical US use during a postcourse practical examination. This is one of the first studies to assess the efficacy of medical students teaching POCUS to midwives and nurses.